2011
DOI: 10.1021/jp208929w
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Magnetism of Mn–Zn–O Systems: Structural, Electronic, and Magnetic Study of Exotic MnO2−δ/ZnO Thin Films

Abstract: The structural, electronic, and magnetic characterization of sputtered MnO2−δ/ZnO films showing room temperature ferromagnetism has been carried out by a number of techniques. To elucidate the origin of the ferromagnetic order, a novel approach by studying XAS and XMCD signals at both Mn and Zn K edges in combination with the macroscopic magnetization measurements has been performed. The analysis of the XAS profile at the Mn edge indicates the coexistence of Mn4+/Mn3+ with a slightly distorted MnO2−δ environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…Notably, Feature G 4 can be split into two peaks (G 4a and G 4b ) (inset in Figure 4c), and the mixed valence states of Mn 3+ and Mn 4+ and their ratios within MnO 2 /extended graphite can be estimated from the ratio of G 4a /G 4b . A decrease in the G 4a /G 4b ratio with the MnO 2 growth within more severe activation degrees of extended graphite may give evidence that the MnO 2 /gra-H contains Mn in a higher oxidation state [34,35]. These XAS results are consistent with the XPS results in Figure 3.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Notably, Feature G 4 can be split into two peaks (G 4a and G 4b ) (inset in Figure 4c), and the mixed valence states of Mn 3+ and Mn 4+ and their ratios within MnO 2 /extended graphite can be estimated from the ratio of G 4a /G 4b . A decrease in the G 4a /G 4b ratio with the MnO 2 growth within more severe activation degrees of extended graphite may give evidence that the MnO 2 /gra-H contains Mn in a higher oxidation state [34,35]. These XAS results are consistent with the XPS results in Figure 3.…”
Section: Resultssupporting
confidence: 86%
“…Notably, Feature G 4 can be split into two peaks (G 4a and G 4b ) (inset in Figure4c), and the mixed valence states of Mn 3+ and Mn 4+ and their ratios within MnO 2 /extended graphite can be estimated from the ratio of G 4a /G 4b . A decrease in the G 4a /G 4b ratio with the MnO 2 growth within more severe activation degrees of extended graphite may give evidence that the MnO 2 /gra-H contains Mn in a higher oxidation state[34,35]. These XAS results are consistent with the XPS results in Figure3.Hence, the overall analysis of the XPS and XAS results demonstrate that extended graphite by electrochemically activated treatment can create defect sites and provide abundant nucleation sites for the growth of MnO 2 ; in the meantime, MnO 2 /extended graphite favorably attain the sp 2 carbon bonds character in graphite sheet, resulting in better electrical conductivity.…”
mentioning
confidence: 99%
“…Rall et al 29 reported non‐stiochicmetric cubic spinel phase as ZnMnO 3– δ and further the structure ZnMnO 3– δ = 3[Zn 2+ ] [Zn 2+ 1/3 Mn 3+ 2/3 Mn 4+ 2/3 □ 1/3 ] O 11/3 with δ = 0.25 of cubic ZnMnO 3 is determined, where □ indicates vacancy at B‐site. Cespedes et al 48 named the Mn–Zn–O system as MnO 2– δ /ZnO where MnO 2– δ has distorted environment with high‐density regions of Mn cations. Therefore, in this communication the secondary phase is identified as non‐stoichiometric defect cubic spinel (DCS)‐ZnMnO 3– δ which is consistent with recently reported ZnMnO 3– δ phase by Rall et al 29.…”
Section: Resultsmentioning
confidence: 99%
“…In the second case, Straumal et al47 have proposed the concept of specific grain boundary area and its influence/role, i.e. on the concentration of surface and interfacial defects present on the nanograined Mn doped ZnO 48. According to this model, the dopant facilitates the long range FM order through the extended network of the chemisorbed species, local lattice distortions, spin disorder and imperfections present at the non‐stiochiometric and highly defect‐rich ZnO grain boundaries, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is a need for reproducibility of a FM signal in undoped oxides systems prepared with the same growth conditions which add to the controversy about the origin of FM. Céspedes et al [15] and Straumal et al [16,17] reported that magnetism in undoped oxides depends on the structural details of the sample, especially at the near-surface regions (surface, grain boundaries, or interfaces). Therefore, since magnetic properties are usually affected by the synthesis conditions, morphology and grain sizes, we have chosen in this study to carry out mechanical milling (MM) treatment for further structure refinement and size reduction of TiO 2 powders.…”
Section: Introductionmentioning
confidence: 99%